Observations on the morphological abnormalitiesin induced bred larvae of some freshwater fishes - Teji, K T; Thomas, K John (Indian Journal of Fisheries, 2014)
Three different species of freshwater fishes, namely Heteropneustes fossilis(stinging catfish), Anabas testudineus (climbing perch), Mystus vitattus (stripeddwarf catfish) were induced bred and morphological studies of the larvae werecarried out. Morphological and behavioural abnormalities were noticed amonglarvae produced through induced breeding techniques in all the three species.Morphological abnormalities were seen in head, trunk and tail region of thelarvae. Under-developed head, deformed trunk, enlarged yolk sac, under-developed barbel, curved tail and vertebral abnormalities were observed.Tunicate larvae (larvae with undetermined growth) were common in thesespecies.